The impacts of total quality management practices in Algerian higher education institutions - Yahiaoui, Fethia; Chergui, Khalil; Aissaoui, Nesreddine; Brika, Said Khalfa Mokhtar; Lamari, Imane Ahmed; Musa, Adam Ahmed; Almezher, Mohmmad (Frontiers in Psychology, 2022)
Algerian universities rely on total quality management. TQM is one of the most successful strategic options for improving the quality of higher education. In addition, achieving academic accreditation and progress in international rankings. The study aims to address relevant contemporary issues by examining the impact of total quality management on the quality of higher education. The data were analyzed using a mixed-method approach; the study was done as a survey, with data collected via questionnaires issued to 610 students. The questionnaire included Likert scale items that were quantitatively evaluated and modelled using structural equation modelling (SEM) using Amos to accomplish the path analysis of the research model. Furthermore, qualitative data was acquired through interviews with 24 professors who are members of the Quality Cells, and qualitative data were evaluated using content analysis with NVivo. The study findings revealed that TQM has a direct and significant impact on the quality of graduates, scientific research, and community service in Algerian universities. The main results have been presented, and recommendations for future research are made.